Cell proliferation and cytokine induction by TNF-α of psoriatic keratinocytes are not different from normal keratinocytes in vitro - Takahashi Hidetoshi; Tsuji Hitomi; Hashimoto Yoshio; Ishida-Yamamoto Akemi; Iizuka Hajime (Wolters Kluwer Medknow Publications, 2009)
Background: Recent studies indicate that various cytokines including tumor necrosis factor-á (TNF-á) play an essential role in the induction and maintenance of psoriatic lesion. Aims: To compare the cell proliferation of keratinocytes by various cytokines and TNF-á-induced cytokine secretion among normal keratinocytes, uninvolved, and involved keratinocytes. Methods: The keratinocytes from normal skin, uninvolved, and involved psoriasis were cultured in the presence of IL-6, IL-8, epidermal growth factor (EGF), hepatocyte growth factor (HGF), transforming growth factor-α (TGF-α) epiregulin, amphiregulin, and TNF-α and then MTT assay for keratinocytes proliferation was performed. Furthermore, TNF-α-induced secretion of IL-6, IL-8, EGF, HGF, TGF-α, epiregulin, and amphiregulin were compared among these keratinocytes. Results: IL-6, IL-8, EFG, TGF-á, epiregulin, and amphiregulin, but not TNF-α increased keratinocyte proliferation of normal, psoriatic uninvolved, and involved skin. The increased cell proliferation by these cytokines and growth factors were not different among the keratinocytes derived from normal skin, uninvolved, and involved psoriasis. The significant induction of TNF-α increased IL-6, IL-8, EGF, HGF, TGF-α, epiregulin, and amphiregulin, but the increase in these cytokines and growth factors were not different among normal skin, uninvolved, and involved psoriasis. Conclusion: Cell proliferation by various cytokines and growth factors and TNF-α-induced cytokine secretion are not different between normal and psoriatic keratinocytes. α